Immunostimulant Effects of Essential Oils of Peppermint and Eucalyptus in Chickens - M. H. H. Awaad*, G. A. Abdel-Alim, K. S. S. Sayed, Kawkab, A. Ahmed1, A. A. Nada2, A. S. Z. Metwalli and A. N. Alkhalaf3 (Pakistan Veterinary Journal, 2010)
The immunostimulatory effects of peppermint and eucalyptus essential oils on cell mediated and/or humoral immunity in chickens vaccinated against Newcastle disease (ND) and Avian Influenza (AI) were investigated. The HI titers against both ND and AI vaccines were higher in volatile oils treated group as compared to the untreated control. The protection percentage reached 35% in volatile oils treated group as compared to 25% in untreated control group and 0% in unvaccinated negative control group on challenge with velogenic viscerotropic ND virus. The positive effect of volatile oils on phagocytic activity of macrophages was significantly (P<0.05) enhanced in treated birds over untreated ones at 14, 28 and 42 days of age. Their effect on serum nitric oxide level revealed significant increase in treated birds versus non-treated ones at 28 and 42 days of age. Lysozyme activity did not show significant change between treated and non-treated groups. In treated birds, scoring of histomorphological changes of major immune organs revealed lymphocytic hyperplasia and activation in Bursa of Fabricious, thymus, spleen and caecal tonsils with a sum of activation score reaching 8 versus 0 in untreated birds. It was concluded that eucalyptus and peppermint oils proved to be able to implement innate-cell mediated, humoral immune response and have a potent immunomodulatory effect in chickens.